Evolution in students’ understanding of thermal physics with increasing complexity - Elon Langbeheim (American Physical Society, 2013)
We analyze the development in students’ understanding of fundamental principles in the context of learning a current interdisciplinary research topic—soft matter—that was adapted to the level of high school students. The topic was introduced in a program for interested 11th grade high school students majoring in chemistry and/or physics, in an off-school setting. Soft matter was presented in a gradual increase in the degree of complexity of the phenomena as well as in the level of the quantitative analysis. We describe the evolution in students’ use of fundamental thermodynamics principles to reason about phase separation—a phenomenon that is ubiquitous in soft matter. In particular, we examine the impact of the use of free energy analysis, a common approach in soft matter, on the understanding of the fundamental principles of thermodynamics. The study used diagnostic questions and classroom observations to gauge the student’s learning. In order to gain insight on the aspects that shape the understanding of the basic principles, we focus on the responses and explanations of two case-study students who represent two trends of evolution in conceptual understanding in the group. We analyze changes in the two case studies’ management of conceptual resources used in their analysis of phase separation, and suggest how their prior knowledge and epistemological framing (a combination of their personal tendencies and their prior exposure to different learning styles) affect their conceptual evolution. Finally, we propose strategies to improve the instruction of these concepts.